Dioscorea esculenta‐induced increase in muscle sex steroid hormones is associated with enhanced insulin sensitivity in a type 2 diabetes rat model. Issue 2 (8th November 2016) - Sato, Koji; Fujita, Satoshi; Iemitsu, Motoyuki
ABSTRACT: The effects of chronic Dioscorea esculenta administration and exercise training on muscle sex steroid hormone levels and insulin resistance in type 2 diabetes rats was assessed. Twenty‐week‐old male Otsuka Long Evans Tokushima Fatty (OLETF) rats were assigned randomly to the control, D. esculenta treatment, D. esculenta with 5α‐reductase inhibitor treatment, or the exercise training groups (running at 25 m/min for 1 h, 5 d/wk; n = 10 each group). Eight weeks of D. esculenta treatment or exercise training significantly attenuated the increase in plasma insulin and fasting glucose levels. Plasma and muscle concentrations of dehydroepiandrosterone and 5adihydrotestosterone (DHT) and the expression of 5α‐reductase increased significantly in the D. esculenta ‐treated and exercise training groups, and both treatments led to the upregulation of glucose transporter‐4 translocation with concomitant increases in PKB and PKC‐ζ/λ phosphorylation. Furthermore, the glucose metabolic clearance rate, which represents insulin sensitivity, increased significantly in both the D. esculenta ‐treated and exercise training groups. These effects were suppressed by administration of the DHT synthetic inhibitor. Together, these findings suggest that the D. esculenta ‐induced increase in muscle sex steroid hormone levels helps decrease insulin resistance in type 2 diabetes.—Sato, K., Fujita, S., Iemitsu, M. Dioscorea esculenta ‐induced increase in muscle sex steroid hormones is associated with enhanced insulin sensitivity in a type 2 diabetes rat model. FASEB J. 31, 793–801 (2017). http://www.fasebj.org